Composition, antibacterial, antioxidant and antiproliferative activities of essential oils from three Origanum species growing wild in Lebanon and Greece. Issue 6 (18th March 2016) - Marrelli, Mariangela; Conforti, Filomena; Formisano, Carmen; Rigano, Daniela; Arnold, Nelly Apostolides; Menichini, Francesco; Senatore, Felice
Abstract : The essential oils from Origanum dictamnus, Origanum libanoticum and Origanum microphyllum were analysed by GC-MS, finding carvacrol, p-cymene, linalool, γ-terpinene and terpinen-4-ol as major components. The antioxidant activity by the DPPH and FRAP tests and the antiproliferative activity against two human cancer cell lines, LoVo and HepG2, were investigated, showing that the essential oil of O. dictamnus was statistically the most inhibitory on both the cell lines, while all the oils exerted a weak antioxidant activity. Furthermore, the samples were tested against 10 Gram-negative and Gram-positive bacteria; all the oils were active on Gram-positive bacteria but O. dictamnus essential oil was the most effective (MIC = 25–50 μg/mL), showing also a good activity against the Gram-negative Escherichia coli (MIC = 50 μg/mL). Data suggest that these essential oils and particularly O. dictamnus oil could be used as valuable new flavours with functional properties for food or nutraceutical products. Abstract :